The Role Model of Rasul Ulul Azmi: An Analytical Study of Akidah Akhlak Material for Madrasah Tsanawiyah - Maulida Yelvi; Putri Adona; Devi Sospita (Al Bahri: Journal of Islamic Education, 2024)
One of the main substances of the Qur'anic content is to contain stories of the past, as a form of Al-Qur'anic da'wah method to mankind, and among the stories is about the Rasul Ulul Azmi. Moving on from this, in this study the author wants to analyse the role model of Rasul Ulul Azmi in Akidah Akhlak learning at Madrasah Tsanawiyah. The research method used is a qualitative method with a content analysis approach, the main source is the Akidah Akhlak textbook published by the Ministry of Religious Affairs of the Republic of Indonesia. After conducting an in-depth analysis, the author found that the structure of the Akidah Akhlak material in Madrasah Tsanawiyah related to the exemplary example of the ulul azmi rasul consists of three sub-themes. The three sub-themes are: i) Understanding Rasul Ulul Azmi, ii) The Main Attributes and Firmness of Rasul Ulul Azmi, iii) The Wisdom of the Exemplary Rasul Ulul Azmi. In the future, the author hopes that this research will have a positive impact, especially in madrasah as a formal educational institution with the characteristic of instilling Islamic values to its students.